Physico-Mechanical Properties of Chemically Treated Jute-Bamboo Hybrid Composites - Liew, Fui Kiew (unimas, 2017)
This research was carried out to analyse the effect of chemical treatments on the jute-bamboo hybrid composite. Hybrid composite strength strongly depends on fiber-matrix adhesion. The hydrophilic nature of natural fibers seriously affects adhesion with a hydrophobic matrix which causes loss of strength. Initially, the jute (Corchorus olitorius) and bamboo (Dendrocalamus asper) fibers were treated with peracetic acid-alkaline, 4-methylcatechol (4MC) at various pH, 3-aminopropyl triethoxysilane (APTS) and hexamethylene diisocyanate (HDI). Hybrid composites were fabricated using treated jute-bamboo (at weight ratio 1:1) hybrid fibers with low density polyethylene (LDPE). Additionally, poly (ethylene‐co‐glycidyl methacrylate) copolymer, tin oxide nanoparticle and montmorillonites (MMT) nanoclay were used in selected hybrid composites series. Tensile tests (tensile strength and Young’s modulus), Fourier transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), dynamic mechanical thermal analysis (DMTA) and water absorption test were used to evaluate the physical, mechanical, thermal and morphological properties of hybrid composites.